Institutional Fragility and Entrepreneurial Activities - Mingzhi Hu; Yinxin Su; Wenping Ye; Yuming Yang (Asia & the Pacific Policy Studies)
ABSTRACT Extensive research has shown that transition economies often experience internal friction, conflicts, and institutional fragility when different institutional dimensions evolve at an uneven pace. However, limited knowledge exists regarding how institutional fragility specifically affects entrepreneurial activities. This study develops a theoretical framework that integrates institutional theory and public choice theory to examine the impact of institutional fragility on entrepreneurship, considering both institutional costs and government intervention. Our findings reveal an inverted U‐shaped relationship between institutional fragility and entrepreneurial activity in China. Furthermore, we find that regional guanxi culture—a key informal institution in China—mitigates this relationship. Overall, this study provides a novel perspective on institutional fragility, offering new insights into how the institutional environment shapes entrepreneurial activity in China.